Cybercrime and information technology : theory and practice - the computer network infostructure and computer security, cybersecurity laws, Internet of Things (IoT) and mobile devices /: theory and practice - the computer network infostructure and computer security, cybersecurity laws, Internet of Things (IoT) and mobile devices. (2021) - (Professor of information technology security), Alexandrou, Alex
No abstract available